(untitled) (TAMADDUN NURI JURNALI, 2024)
This article critically examines the scope, criteria, and implementation challenges of green box subsidies within the AoA framework. Special attention is given to the nuanced conditions for qualifying subsidies, the balance between social objectives and trade obligations, and the implications for developing countries, particularly in achieving food security.